2020
DOI: 10.1016/j.bioflm.2020.100024
|View full text |Cite
|
Sign up to set email alerts
|

Building a better biofilm - Formation of in vivo-like biofilm structures by Pseudomonas aeruginosa in a porcine model of cystic fibrosis lung infection

Abstract: Pseudomonas aeruginosa biofilm infections in the cystic fibrosis (CF) lung are highly resistant to current antimicrobial treatments and are associated with increased mortality rates. The existing models for such infections are not able to reliably mimic the clinical biofilms observed. We aimed to further optimise an ex vivo pig lung (EVPL) model for P. aeruginosa CF lung infection that can be used to increase understanding of chronic CF biofilm infection… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 61 publications
(64 reference statements)
4
44
0
Order By: Relevance
“…Figure 1 represents a schematic diagram of the work flow as previously described. Supplementary Figures S3 , S4 show pieces of tissues infected with P. aeruginosa strains after 7 days of biofilm formation and the mucoid phenotype of the strains in the tissues, respectively, to represent chronic CF infection ( Harrington et al, 2020 ). Our previous work with the EVPL model confirms that P. aeruginosa forms structured biofilms in this model [Alcian blue staining confirms presence of exopolysaccharide matrix, and mutant studies showed formation of structured aggregates on tissue required the gacS/gacA pathway and pel polysaccharide ( Harrington et al, 2020 )].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 represents a schematic diagram of the work flow as previously described. Supplementary Figures S3 , S4 show pieces of tissues infected with P. aeruginosa strains after 7 days of biofilm formation and the mucoid phenotype of the strains in the tissues, respectively, to represent chronic CF infection ( Harrington et al, 2020 ). Our previous work with the EVPL model confirms that P. aeruginosa forms structured biofilms in this model [Alcian blue staining confirms presence of exopolysaccharide matrix, and mutant studies showed formation of structured aggregates on tissue required the gacS/gacA pathway and pel polysaccharide ( Harrington et al, 2020 )].…”
Section: Resultsmentioning
confidence: 99%
“…50% of the original BODIPY-colistin dose being recovered, consistent with colistin binding plastic (data not shown). model, (24 )), this suggests a sensible maximum biofilm volume to use is 8.8 µl. Figure 3b shows the predicted BODIPY-colistin concentrations in the biofilms assuming this volume.…”
Section: Pa14 Sed6 Sed8mentioning
confidence: 97%
“…aeruginosa biofilms depending on strain and culture conditions. We aimed first to compare the tolerance of P. aeruginosa to colistin using planktonic microdilution in standard antibiotic susceptibility testing medium (cation-adjusted Muller-Hinton broth, caMHB) and synthetic CF sputum medium (SCFM, (23)); biofilm eradication assays using the same media in a Calgary device; and in an ex vivo model of CF biofilm which combines SCFM and pig bronchiolar tissue (24,25). We then aimed to use fluorescently-labelled colistin to measure the percentage of a dose which was able to enter the biofilm matrix in the ex vivo CF model.…”
Section: Full Textmentioning
confidence: 99%
See 1 more Smart Citation
“…In an in vivo murine chronic wound model, oxidative stress and community composition alone do not characterize the microbial community metabolism (Dhall et al, 2014 ). Similarly, tissue models, including an ex vivo porcine lung model, investigate only the growth of a single pathogen at a time (Harrison et al, 2014 ; Dumigan et al, 2019 ; Harrington et al, 2020 ; Sweeney et al, 2019 ). To better understand chronic infections, it is important to consider the entire microbial community.…”
Section: Introductionmentioning
confidence: 99%